O que podem uma Educação Infantil, uma pesquisa e outras caduquices da vida quando ascendem à infância? - AMANDA SILVA DE MEDEIROS (2023)
There is one question that drives this research to work: how much does childhood fit into Preschool Education? Inhabits then, a school of preschool education in the municipality of Campo Grande/MS, in order to experience and problematize, along with fourteen three-year-old children and their three teachers, the childhoods that occupy this space. It is caught up in the bureaucracy of doing research with children, of doing research amid a pandemic, of proposing an open research that is produced with what goes through it. In the midst of these stumbles, its discussed Preschool Education as an educational policy that is guided by a chronological and formative childhood that, since ancient times, places the child in a place of marginality, where he is formed, molded, and taught to be a child by adults, always waiting for what he will be when he grows up. But then, another childhood, which is an opening and time, presents itself as a possibility and a revolution. A childhood present in the children's productions, in the fissures created by them, and that, for being a dis-age, also reaches the research. A time of childishness that can be reached by anyone. This childhood is a potency for another preschool to be experienced, a more childlike preschool. Thus, in the encounter with the children's childhoods, one also ascends to the childhoods of those who allow themselves to experience and play with them. Thus, in the opening, in the invitation, it is composed with images, speeches, experiences, inventing in the indistinction between adult and child that, by interlacing their hands, create the potency of reaching a childhood that crumbles what is set, what is expected, the sameness, releasing the world from its lapses. The intention is, then, not only to constitute a thesis that announces another possibility for preschool Education - another urgent possibility, produced with childhoods - but also as an invitation so that those who stumble upon this production may also ascend to childhood.